Pengaruh Model Pembelajaran Inkuiri Terhadap Hasil Belajar Siswa Pada Materi Sejarah Perkembangan Teknologi Informasi dan Komunikasi - Wiwin Wiwin; Veronika Asianti; Ikmal Sodikin; Abdul Mokhlis; Rini Juharyati; Firda Aulia Safitri (Jurnal Indonesia Sosial Teknologi, 2022)
This study aims to describe the Influence of the Inquiry Learning Model on Student Learning Outcomes on the History of Information and Communication Technology Development in Class 7 MTs Al-Hadari An-Nawawi Kumpai. This study uses a quantitative approach, the method used in this study is the experimental method. The form of this research is a quasi-experimental design (quasi-experimental) with a nonequivalent control group design. The population studied in this study were the 7th grade students of MTs Al-Hadari An-Nawawi Kumpai, totaling 48 people. The sampling technique in this study used a saturated 2 sampling technique. So that there are 24 people in 7A class and 24 people in 7B class. The data measurement technique used in this study is a measurement technique. The tool used to collect data in this study was a test. This research uses quantitative descriptive.